2010
DOI: 10.1002/pi.2848
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic films of UV‐curable fluorinated epoxy acrylate resins

Abstract: Photopolymerization processes are often used in industrial applications because of their solvent-free formulations and various advantages over conventional thermal processes. Fluorinated monomers and oligomers yield coatings of great interest because of the peculiar characteristics of fluorine atoms: these coatings show hydrophobicity, chemical stability, weathering resistance, etc. Novel UV-curable fluorinated epoxy acrylate oligomers were synthesized from 1H,1H-perfluorohexan-1-ol, 1,6-hexamethylene diisocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…These results were well consistent with the contact angle measurement. Data from XPS analysis was a strong evidence confirming the fact that long fluorinated side chains, which have greater thermodynamic driving force to migrate to the surface due to the incompatibility with the matrix, are more efficient and effective to migrate and concentrate on the surface than short pendent fluorinated group …”
Section: Resultsmentioning
confidence: 77%
“…These results were well consistent with the contact angle measurement. Data from XPS analysis was a strong evidence confirming the fact that long fluorinated side chains, which have greater thermodynamic driving force to migrate to the surface due to the incompatibility with the matrix, are more efficient and effective to migrate and concentrate on the surface than short pendent fluorinated group …”
Section: Resultsmentioning
confidence: 77%
“… with the help of microscopy images. Number of researchers have shown that PDMS polyol and fluoro polyol contributes to phase separation and can affect impact resistance of their films. It is interesting, however, that the cross‐cut adhesion was not affected by this possible phase morphology.…”
Section: Resultsmentioning
confidence: 99%
“…The photopolymerization process is of great interest in industrial applications because of its superior features over conventional heat curing systems, such as lower energy consumption, less environmental pollution, lower process costs, high chemical stability and very rapid curing even at ambient temperatures (15)(16)(17). Because of these advantages, the photopolymerization process has been used widely in the coating and paint sectors (18).…”
Section: Introductionmentioning
confidence: 99%